Pengaruh Lingkungan Kerja , Motivasi Kerja dan Disiplin Kerja Terhadap Kepuasan Kerja Karyawan (Studi Pada Karyawan Richeese Cabang Mojokerto) - Wilda Rahmawati; Abdul Kodir Djaelani; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2022)
Abtsract This study aims to determine the effect of work environment, work motivation and work discipline on employee job satisfaction. The sampling technique used is saturated sampling, the data sample is 37 respondents. Methods of data collection using a questionnaire. The data analysis technique used in this research is multiple linear regression. The results showed that simultaneously work environment, work motivation, and work discipline had a positive and significant effect on employee job satisfaction. Partially the work environment has a positive and significant effect on employee job satisfaction, work motivation also has a significant positive effect on employee job satisfaction, work discipline has a significant positive effect on employee job satisfaction Keywords: Work Environment, Work Motivation, Work Discipline, Job Satisfaction.